Hyperprolactinemia as a side effect of using antipsychotics In Schizophrenic Patients - Anwar, Syaiful; Khairina (Faculty of Medicine, Universitas Airlangga, 2023)
Introductions: Antipsychotics are still the mainstay of schizophrenia management. Antipsychotics are antagonistic to postsynaptic dopamine receptors in the brain. Blockade of dopamine receptors in the tuberoinfundibular pathway by antipsychotics will cause the side effect of hyperprolactinemia. Objectives: This review describes hyperprolactinemia induced by antipsychotic use and its clinical effects, monitoring, and management. Methods: reference search through Google Scholar with keywords schizophrenia, antipsychotics, prolactin, hyperprolactinemia, clinical effects of hyperprolactinemia, diagnosis of hyperprolactinemia, monitoring of hyperprolactinemia, management of hyperprolactinemia. Results: Clinicians need to take a diagnostic approach to identify the etiology of hyperprolactinemia, monitor the clinical symptoms of hyperprolactinemia during the administration of antipsychotics, and immediately carry out management according to existing strategies by considering some general principles and considerations. Conclusions: Schizophrenia is a severe mental disorder that lasts long, requiring long-term and continuous therapy. Administration of antipsychotics is still a mainstay in the management of schizophrenia. Antipsychotics are antagonists to postsynaptic dopamine receptors in the brain. The antipsychotic effect of blocking dopamine receptors not only improves the symptoms of schizophrenia but also causes side effects. The side effect when the tuberoinfundibular dopamine pathway is blocked is an increase in prolactin levels called hyperprolactinemia.